On the Explanations of the Meanings of Lithuanian Proverbs in Constant von Wurzbach ’s collection Sprichwörter der Polen historisch erläutert, mit Hinblick auf die eigenthümlichsten der Lithauer ... (1852) - Plaušinaitytė, Lina (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstracts in English and German]This article focuses on the collection of proverbs, titled Die Sprichwörter der Polen historisch erläutert, mit Hinblick auf die eigenthümlichsten der Lithauer, Ruthenen, Serben und Slovenen und verglichen mit ähnlichen andrer Nationen (1852), which comprises, among many Polish and other Slavonic proverbs, 93 Lithuanian sayings. The collection was assembled by the Austrian writer and famous biographer Constant Ritter von Wurzbach-Tannenberg, who is mostly known as the sole compiler of the 60-volume reference book Biographisches Lexikon des Kaisertums Österreich (1856–1891) as well as the author of various texts dealing with different aspects of cultural history. The given collection of proverbs represents the first printed publication of Lithuanian proverbs in a German book (apart from the lexicographical sources), through which they have made their way into the eminent proverb collection of Karl Wander, the largest comparative proverb collection of the 19th century in the German language, and thus became accessible to an even larger reading public. The proverbs in Wurzbach’s collection are grouped on the basis of thematic key notions. Most of the proverbs are supplied with a large explanatory part, which makes this collection so unique. The explanations not only provide information about the meaning, origin and use of proverbs, but also convey a rather positive attitude of the author concerning their content, wit and the image of Lithuanians as a whole. The current article analyzes the way Wurzbach presents Lithuanian proverbs, explains their meanings and, following the Romantic idea of the natures of nations being represented in their languages, makes suggestions about the Lithuanian character. Furthermore, in this article, special attention is given to the sources of the Lithuanian proverbs. One of the sources that Wurzbach mentions in the introduction to his book is the collection of Lithuanian proverbs in the Polish language by Adam Jucewicz (1842). The research shows, however, that this source can only account for about one third of all Lithuanian proverbs in Wurzbach’s collection. The historical works of Theodor Narbutt, also mentioned in Wurzbach’s collection, could not have served as a source for more than one or two sayings, either. The question of other sources of Lithuanian proverbs in the Wurzbach collection requires yet some further study. Litauische Sprichwörter und ihre Bedeutungs interpretationen in der Sprichwörtersammlung Constant von Wurzbachs Sprichwörter der Polen historisch erläutert, mit Hinblick auf die eigenthümlichsten der Lithauer ... (1852)Der vorliegende Beitrag behandelt die Sammlung polnischer und anderer slawischer Sprichwörter Die Sprichwörter der Polen historisch erläutert, mit Hinblick auf die eigenthümlichsten der Lithauer, Ruthenen, Serben und Slovenen und verglichen mit ähnlichen andrer Nationen. In der Sammlung wurden unter anderem 93 litauische Sprichwörter veröffentlicht. Der Verfasser dieser Sammlung ist der berühmte österreichische Biograph Constant Ritter von Wurzbach-Tannenberg, Autor des 60-bändigen Biographischen Lexikons des Kaisertums Österreich (1856–1891) sowie zahlreicher weiterer kulturhistorischer Schriften. Bei dieser Sammlung handelt es sich um die erste Publikation litauischer Sprichwörter in einer deutschsprachigen Sprichwörtersammlung. Zum einen trug die Veröffentlichung litauischer Sprichwörter direkt zur Verbreitung der Kenntnisse vom litauischen Volk, seiner Sprache und Kultur bei. Zum anderen hatte die Publikation indirekt als Vermittler gedient: aus diesem Werk sind litauische Sprichwörter in die große Sprichwörtersammlung Karl Wanders gelangt, von wo aus sie einem noch größeren Leserpublikum zugänglich geworden sind. Die thematisch geordnete Sammlung von Wurzbach zeichnet sich dadurch aus, dass den Sprichwörtern Erklärungen beigegeben werden, die nicht nur ihren Ursprung und Gebrauch kommentieren, sondern auch meistens positive Urteile des Verfassers über ihren Inhalt und Witz oder über das litauische Volk insgesamt enthalten. Im Aufsatz wird die Präsentationsweise der Sprichwörter analysiert und auf die Struktur sowie einige inhaltliche Besonderheiten der Bedeutungserklärungen eingegangen. Außerdem wird das Verhältnis der litauischen Sprichwörter zu der im Literaturverzeichnis angegebenen Quelle, der polnischsprachigen Sammlung litauischer Sprichwörter von Adam Jucewicz (1840), besprochen und festgestellt, dass neben dieser Quelle Wurzbach noch mindestens eine weitere Sprichwörtersammlung benutzt haben soll. Ihre genaue Bestimmung steht allerdings noch aus.